Loading and elution characteristics of quadrasphere microspheres loaded with bevacizumab. (August 2017) - Oselkin, Martin; Sedora-Roman, Neda I; Pukenas, Bryan A; Kung, David; Hurst, Robert W
Aim: Super absorbent polyvinyl alcohol-sodium acrylate copolymer microspheres, Quadrasphere microspheres (QSM), are commonly used for drug-eluting bead therapy, however, the literature only reports its use with small molecule chemotherapeutics. This study evaluates the loading and elution characteristics of bevacizumab-loaded QSM.Methods & results: A single vial of QSM was reconstituted with 200 mg of bevacizumab. Drug concentration was determined by ELISA immunoassay. At approximately 90 min, there was maximal loading at 59% of the starting dose. In vitro elution demonstrated 52% of bound bevacizumab was released within the first hour and 68% by 16 h.Conclusion: Bevacizumab can load onto QSM and elute over time. This targeted delivery vehicle may potentially result in more effective treatment and fewer complications related to systemic toxicity.